An Analysis on Some Improvement of Routing Protocols in Mobile Ad Hoc Networks: Enhancing Routing Protocols in Mobile Ad Hoc Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wireless ad hoc networks utilize multi-hop radio relaying and are capable of operating without the support of any fixed infrastructure. In Wireless ad hoc networks or Mobile ad hoc networks (MANETs), the responsibility of routing is exchanging the route information and finding a feasible path to a destination. To discover a route to a particular destination node, existing routing protocols can be categorized into three main categories such as Proactive or table-driven routing protocols, Reactive or on-demand routing protocols and Hybrid routing protocols. On-demand routing protocols increase the required path when it is necessary, by using connection establishment technique. The on-demand routing protocols initiate Route discovery (RREQ) packet to discover the path between source node and destination node. Every node receiving the RREQ message will retransmit it to all its neighbors. This broadcasting is referred to as blind flooding. This can lead to unnecessary redundant retransmissions, causing high channel contention and packet collisions in the network, a phenomenon called a broadcast storm.In existing probabilistic based broadcast algorithms, each forwarding node is permitted to rebroadcast a received packet with a fixed forwarding probability. An innovative probabilistic route discovery method is proposed to decrease the dissemination of route request packets. To improve the fixed probabilistic mechanism, the adjusted route discovery concept is proposed based on the density. If possible, the forwarding probability should be high for a node positioned in a sparse region of the network while comparatively lower for a node situated in a denser region of the network. The performance of this technique is superior than the fixed probabilistic route discovery mechanism.